Analysis of the Influence of Price, Promotion and Company Image on Decisions on Using Winnie's Wedding Organizer & Decoration Services in Sukabumi City - Saepudin Ciamis; Aryanti Ratnawati; Vanny Decianita (Jurnal Ekonomi Manajemen Perbankan, 2021)
This study aims to examine the relationship between price, promotion and corporate image on the decision to use Winnie's Wedding Organizer & Decoration services in Sukabumi City. The research was conducted on Winnie's Wedding Organizer & Decoration service users in Sukabumi in the period 2017 - 2019, with a sample of 86 customers. The hypothesis formulated in this study is as follows: "It is suspected that price, promotion, and company image influence the decision to use Winnie's Wedding Organizer & Decoration services in Sukabumi City".Based on the analysis and discussion obtained; regression equation Y = 6,697 - 0,180X1 + 0,057X2 + 0,930X3 + ∈. The total correlation (correlation) between price, promotion and company image with the decision to use Winnie's Wedding Organizer & Decoration in Sukabumi is in the strong category (0.603). The magnitude of the effect of total price, promotion and company image on the decision to use Winnie's Wedding Organizer & Decoration services in Sukabumi City (determination) is 36.4%, the remaining 63.6% is influenced by other factors not examined.